Retrato da estrutura patriarcal latino-americana: um olhar para as violências contra as mulheres em La casa de los espíritus - Opazo, Andreia Piechontcoski Uribe (2023)
This work consists in the study of the work La casa de los espíritus ([1982] 2007a) ([1982] 2007a), by Isabel Allende, aiming to reflect on the interactions between the patriarchal structures of Latin American society present in the novel, in addition to the investigation of the resumption of the memory of the female characters through fiction. Therefore, this research is based on the study of the work, both within the context of female authorship literature in Latin America and the patriarchal society itself. In this sense, it was intended to establish an intertextual dialogue between what is materialized in the novel, the forms of oppression in the context, and the narrative strategies for the resumption of memory of Latin American women. It departs, therefore, from the perspective of Comparative Literature, relying on the concept of intertextuality seen in Kristeva ([1969] 2012), Carvalhal (2006) and Nitrini (2021), since social and historical discourses, feminist theory and The work. The research is based on the theorists Navarro (1995), Schmidt (1995), Guardía (2013) and Zolin (2019a), to reflect on female authorship and the context of Latin America; as well as, when one glimpses the reception of literary criticism towards Isabel Allende, using as a basis the studies of Coddou (1998;1991), Godoy (2008) and Castillo (2014). Finally, to deal with the representation of Latin American women through the female characters in the novel and the rescue of their memory, the studies of Montecino (1996), Segato (2003) and Galindo (2013) were used as a theoretical basis, about patriarchal and gender relations in Latin America; in addition to the theoretical contribution seen in Le Goff (1992), Nora (1993) and Bernd (2013) on memory. With regard to the expected results, the aim is to verify the direct influence between the work analyzed and studies of gender and patriarchal culture in Latin America and, nevertheless, the novel as a materialization of female authorship as a memorial artifact for women.